Estimation of Genetic Parameters for Growth and Reproduction Traits in Exopalaemon carinicauda - Chengwei WANG; Jiajia WANG; Xiuhong ZHANG; Shuai TANG; Peichun WANG; Jian LI; Jitao LI (Progress in Fishery Sciences)
The ridgetail white shrimp (Exopalaemon carinicauda), belonging to the Palaemonidae family of crustaceans, is an economically important small-to-medium-sized shrimp in China that is naturally distributed on the coasts of the Yellow and Bohai Seas. Due to its rapid growth and high tolerance for environmental stress, the scale at which E. carinicauda is cultured has expanded in recent years. The reproductive performance of broodstock is crucial to the yield and quality of larvae, as the egg production of E. carinicauda is much lower than that of other economically important shrimps. Meanwhile, E. carinicauda seedling production mainly relies on wild shrimp or breeding parents, resulting in low fertility and poor seed quality, such that the cultivation of E. carinicauda is often hindered by a slow growth rate and poor disease resistance, seriously limiting the development of the E. carinicauda farming industry. Optimizing growth and reproductive traits is vital for the animal aquaculture industry, as these traits are crucial for developing high-quality seedlings and are directly related to yield. Cultivating new varieties with high fertility and fast growth rates can effectively improve the aquaculture of E. carinicauda. In this study, we estimated the genetic parameters of growth and reproduction traits in E. carinicauda. We constructed 40 full-sibling lines of E. carinicauda and 25 half-sibling lines by pairing one male with two females. Thirty shrimps were randomly selected from each line at 50 d and 80 d of age, and the body length, total abdominal length, and body weight were measured to calculate the genetic parameters. The number of eggs, body length, body weight, and incubation time of the first spawning were measured to ensure that the culture conditions for each line were consistent. The main baits used during incubation were folded brachyuran rotifers (Brachinonus plicatilis) and brine shrimp (Artemia sinica). The heritability, phenotypic correlations, and genetic correlations of body weight, body length, total abdominal length traits, time of first spawning, absolute egg count, egg count per unit of body length, and egg count per unit of body weight in E. carinicauda were estimated at the ages of 50 and 80 d using a general linear model. The results showed that the heritability estimate values for body length, total abdominal length, and body weight at 50 d were approximately 0.27–0.69, 0.31–0.44, and 0.20–0.65, respectively, and those for body length, total abdominal length, and body weight at 80 d were approximately 0.39–0.54, 0.31–0.47, and 0.33–0.71, respectively. The heritability estimate values for the number of eggs, the number of eggs per unit of body length, the number of eggs per unit of body weight, and the time of the first spawning were approximately 0.45–0.52, 0.30–0.49, 0.43–0.48, and 0.33–0.77, respectively. The heritability estimate values for all three growth-related traits and four reproduction traits almost reached the level of medium-high heritability. The heritability estimate values for growth and reproduction traits based on full siblings reached a highly significant level according to t-tests. Therefore, the unbiased estimates of narrow-sense heritability for growth and reproduction traits were those estimated by the full-sibling variance component. The phenotypic and genetic correlations for growth and reproduction traits were approximately 0–0.756 9 and –0.006 5–0.951 4, respectively. The genetic correlation coefficients of body weight with body length and egg count were 0.951 4 and 0.205 8, respectively. The phenotypic correlation coefficients of body weight with body length and egg count were 0.742 0 and 0.212 4, respectively. However, the genetic and phenotypic correlations between body length and egg count were poor. Therefore, we suggest that body length and egg count be set as two different targets in breeding programs. The results indicate that the heritability estimate values for body length, total abdominal length, and body weight at 50 and 80 d and for reproduction traits including egg count, egg count per unit length or weight, and time of first spawning almost reached the level of medium-high heritability. The growth and reproductive traits of E. carinicauda can be selected through individual or population-phenotypic selection. The above results provide important basic data to support the breeding of E. carinicauda and have considerable application value for future breeding programs.